1987
DOI: 10.1182/blood.v69.2.682.682
|View full text |Cite
|
Sign up to set email alerts
|

Control of hemopoiesis by a bone marrow stromal cell clone: lipopolysaccharide- and interleukin-1-inducible production of colony- stimulating factors

Abstract: A stromal cell line, GY30, was cloned from mouse bone marrow adherent cell layers. In culture, GY30 cells sustain the production of granulocyte-macrophage progenitor cells (GM-CFU) but fail to support the survival of pluripotential stem cells (CFU-S). GY30 cells secrete two growth factor activities distinct from interleukin-3 (IL-3), IL-2, and macrophage colony-stimulating factor (M-CSF) but functionally similar to GM-CSF and G-CSF. The production of both CSFs is increased 70- to 200-fold by treating GY30 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…37,38 A number of different cell types including T lymphocytes, macrophages, and cancer cells produce GM-CSF. 37,40 In most cases, inflammatory stimuli induce the production of GM-CSF, including typical inflammatory mediators/inducers, such as tumor necrosis factor-a, 41 IL-1, 42 and LPS. 42 In addition to GM-CSF, IL-3 enhanced Siglec-F expression (see Supplementary material, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 A number of different cell types including T lymphocytes, macrophages, and cancer cells produce GM-CSF. 37,40 In most cases, inflammatory stimuli induce the production of GM-CSF, including typical inflammatory mediators/inducers, such as tumor necrosis factor-a, 41 IL-1, 42 and LPS. 42 In addition to GM-CSF, IL-3 enhanced Siglec-F expression (see Supplementary material, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its biological activities include induction of various cytokines. IL-1 has been shown to induce the production of granulocytemacrophage colony-stimulating factor [5][6][7][8][9][10][11][12][13], granulocyte CSF (G-CSF) [9][10][11][12] and B-cell stimulatory factor-2/interleukin-6/interferon-fl2 (IFN-~2)/26-kDa protein [14][15][16][17]. Recently it has also been reported that IL-1 can induce its own synthesis [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation and differentiation of hemopoietic progenitor cells and the biological activities of mature cells are thought to be controlled at least in part by a family of hemopoietic growth factors including those referred to as the colony-stimulating factors (CSF) (Metcalf, 1984). While a wide variety of murine cell types have been shown to produce specific hemopoietic growth factor mRNAs and bioactivities in vitro (Metcalf, 1984;Rennick et al, 1987;Oppenheim et al, 1986;Dexter, 1987;Arai et al, 1986), relatively little is known about the sites of production in vivo. Indeed, for such factors as IL-2 and IL-3 no evidence for production in vivo has yet been reported.…”
mentioning
confidence: 99%